DINAMIKA HUBUNGAN BILATERAL AUSTRALIAINDONESIA PADA MASA PERDANA MENTERI JOHN HOWARD TAHUN 1996-2007 - Fatmawati Fatmawati; Tarunasena Ma'moer (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2018)
Prime Minister John Howard’s behaviour often considered conservative and “Anti- Asian”, no exception to Indonesia. John Howard viewed Indonesia did not have a strategic position for Australia’s national interests. This study answered the question on “how did the dynamic of Australia-Indonesia bilateral relations at Prime Minister John Howard’s era in 1996-2007?”. At his administration, John Howard issued numbers of policy towards Indonesia, which are the policy related to East Timor issue, counterterrorism cooperation, the policy of Pacific Solution, assistance for tsunami disaster in Aceh that happened in 2004. These policies apparently made impacts to Australia- Indonesia bilateral relations. During eleven years administration of Prime Minister John Howard, the bilateral relations between Australia-Indonesia has experienced its dynamics of ebb and flow. These dynamics primarily caused by policies that Prime Minister John Howard issued, which gave more benefit to the Australian Government and created imbalance relations between two countries. Therefore, it became more interesting to be discussed for further study regarding which policies that gave more benefit for the Australian Government and in a contrary gave less benefit to Indonesian Government, thus the position of two countries became an imbalance in bilateral relations context. This research is expected to be a reference for other researchers who will examine the bilateral relations between Australia-Indonesia in John Howard’s era because there are still many aspects between the two countries relations that have not been elaborated by the researcher, namely economic, education and socio-cultural.